World Bank Research Digest, Vol. 6(1) - World Bank (Washington, DC, 2014)
In this issue: gross capital flows: dynamics and crises; crisis recovery and the role of credit: do phoenix miracles exist? Decentralization and municipal spending ability in developing countries; when starting with the most expensive mitigation options makes sense; evaluating the impact of trade interventions; and the influence of society on preferences.